2006
DOI: 10.1002/uog.2964
|View full text |Cite
|
Sign up to set email alerts
|

OC104: Soft tissue parameters improve the precision of fetal weight estimation

Abstract: Objectives: Current weight estimation models do not consider the contribution of fetal soft tissue to fetal weight. We have investigated new weight estimation models that use a combination of conventional biometry and soft tissue parameters. Methods: A cross-sectional study of 248 fetuses was performed using 3DUS to acquire standard biometry (BPD, AC, FDL), fractional arm volume (Avol), and fractional thigh volume (TVol) within 4 days of delivery. Multiple linear regression was used to develop a 'modified Hadl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…The models yielding the best results were those including BPD, AC and thigh volume. Somewhat surprisingly, we found the 2D method of FW estimation to perform better than the Lee 1 formula10 and similarly to the Lee 2 formula11. It could be argued that this may have been due to the examiner lacking sufficient experience in the use of 3D ultrasound imaging.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…The models yielding the best results were those including BPD, AC and thigh volume. Somewhat surprisingly, we found the 2D method of FW estimation to perform better than the Lee 1 formula10 and similarly to the Lee 2 formula11. It could be argued that this may have been due to the examiner lacking sufficient experience in the use of 3D ultrasound imaging.…”
Section: Discussionmentioning
confidence: 61%
“…By using 3D ultrasound imaging it is possible to generate volume data sets of the fetus. There is published evidence that fetal limb volume measurements and abdominal volume measurements may be valuable in estimating FW2, 9–14. Lee et al have developed several BW prediction models using 3D volumetric measurements of thigh, arm and abdomen, including one or more parameters1, 9–11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding corroborates those of a previous study of incorporation of the fractional fetal thigh volume into the estimation of fetal weight. 18,19 We found fetal weight estimates that included the fractional thigh volume to be more frequently within 15% of actual birth weights and to be consistently accurate across a wide range of birth weights compared with traditional 2D biometric measurements. A larger study may be necessary to corroborate this finding given the small subset of patients who had birth weights of less than 2500 g. We also observed that the fetal fractional thigh and upper arm volumes correlated significantly with neonatal skin fold measurements and markers of neonatal obesity.…”
Section: Discussionmentioning
confidence: 79%